Gambaran Pengetahuan Akseptor KB Terhadap Efek Samping Penggunaan Kontrasepsi Hormonal Di Puskesmas Bumi Restu Provinsi Lampung - Yustina Nova Kriswidiani; Margaretha Kusmiyanti; Willhelmus Hary Susilo (PT. Pubsains Nur Cendekia, 2024)
Family planning (KB) is an effort to regulate the birth of children, the distance and ideal age at birth to create a quality family. The large number of family planning acceptors at the Bumi Restu Community Health Center who complain about the side effects that occur when using hormonal contraceptives causes some acceptors to become anxious and ultimately drop out, this can be influenced by the knowledge possessed by the acceptors. The aim of this research is to see a description of the knowledge of family planning acceptors regarding the side effects of using hormonal contraception at the Bumi Restu Community Health Center. The research uses descriptive analytics with a quantitative approach method. The population in this study was 309 people using a purposive sampling technique and the results obtained were 75 respondents plus 10% to anticipate respondents who dropped out, so the sample in this study was 82 respondents in the period February 2022. Data collection was taken from primary data using a questionnaire which is distributed to hormonal birth control acceptors. Statistical tests use frequency distributions and percentages. The research results obtained were that of the 82 respondents, 15 respondents (18.3%) had poor knowledge, 39 respondents (47.6%) had sufficient knowledge, and 28 respondents (34.1%) had good knowledge. Conclusion; The majority of knowledge possessed by family planning acceptors at the Bumi Restu Community Health Center is sufficient. Suggestions for further research can be carried out on the role of health workers, not just family planning acceptors.